Blimp-1 Expression as an Exhaustion Transcription Factor in Chronic Lymphocytic Leukemia - Saeid Taghiloo; Esmaeil Allahmoradi; Mohsen Tehrani; Ghasem Janbabaei; Ramin Shekarriz; Hossein Asgarian-Omran (Research in Molecular Medicine, 2017)
Background: PPreviously, it was shown that exhausted CD4+ and CD8+ T cells in chronic lymphocytic leukemia (CLL) co-express the two immune-inhibitory receptors, Tim-3 and PD-1. Present study investigated the expression of Blimp-1, a transcription factor involved in T cell exhaustion, in patients with CLL. Materials and Methods: Peripheral blood mononuclear cells were collected from 25 untreated CLL patients and 15 sex- and age-matched normal subjects. CLL patients were clinically classified according to the Rai staging system. The relative expression of Blimp-1 mRNA was determined by quantitative Real Time Polymerase Chain Reaction (qRT-PCR) after normalization with β-actin. Results: Expression of Blimp-1 mRNA was much higher in CLL patients than in normal controls (p=0.001). Moreover, Blimp-1 was more expressed in patients with advanced clinical stages of CLL compared to those with early stages of the disease (p=0.01). Interestingly, the Blimp-1 expression was correlated with the frequencies of exhausted Tim-3+/PD-1+/CD4+ and Tim-3+/PD-1+/CD8+ T cells in CLL patients. Conclusion: Our results highlight the role of Blimp-1 transcription factor in T cell exhaustion of CLL.